Adding a “Notch” to Cardiovascular Disease Therapeutics: A MicroRNA-Based Approach - Marracino, Luisa; Fortini, Francesca; Bouhamida, Esmaa; Camponogara, Francesca; Severi, Paolo; Mazzoni, Elisa; Patergnani, Simone; D’Aniello, Emanuele; Campana, Roberta; Pinton, Paolo; Martini, Fernanda; Tognon, Mauro; et al. (Frontiers in Cell and Developmental Biology, 2021)
Dysregulation of the Notch pathway is implicated in the pathophysiology of cardiovascular diseases (CVDs), but, as of today, therapies based on the re-establishing the physiological levels of Notch in the heart and vessels are not available. A possible reason is the context-dependent role of Notch in the cardiovascular system, which would require a finely tuned, cell-specific approach. MicroRNAs (miRNAs) are short functional endogenous, non-coding RNA sequences able to regulate gene expression at post-transcriptional levels influencing most, if not all, biological processes. Dysregulation of miRNAs expression is implicated in the molecular mechanisms underlying many CVDs. Notch is regulated and regulates a large number of miRNAs expressed in the cardiovascular system and, thus, targeting these miRNAs could represent an avenue to be explored to target Notch for CVDs. In this Review, we provide an overview of both established and potential, based on evidence in other pathologies, crosstalks between miRNAs and Notch in cellular processes underlying atherosclerosis, myocardial ischemia, heart failure, calcification of aortic valve, and arrhythmias. We also discuss the potential advantages, as well as the challenges, of using miRNAs for a Notch-based approach for the diagnosis and treatment of the most common CVDs.